2014
DOI: 10.2989/20702620.2014.899058
|View full text |Cite
|
Sign up to set email alerts
|

Culture-independent detection and quantification ofFusarium circinatumin a pine-producing seedling nursery

Abstract: The primary symptoms associated with Fusarium circinatum infection in pine seedling nurseries are root and collar rot, shoot and tip die-back and seedling mortality. Management of this pathogen in nurseries usually involves the integration of various strategies relating to sanitation, insect control and fungicide treatment. The overall goal of this study was to use quantitative real-time PCR (qPCR) to detect and quantify the airborne inoculum of F. circinatum in a commercial pine seedling nursery. For this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…Similar results with the constant presence of F. circinatum throughout the whole year were obtained in other areas such as northern California [28] and South Africa [39]. This finding means that F. circinatum in Galicia can develop the infection at any time of the year whenever suitable environmental conditions and susceptible hosts are available for spore germination, as was expected from the calculation of models of spread [26,40].…”
Section: Seasonal Spore Dispersalsupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results with the constant presence of F. circinatum throughout the whole year were obtained in other areas such as northern California [28] and South Africa [39]. This finding means that F. circinatum in Galicia can develop the infection at any time of the year whenever suitable environmental conditions and susceptible hosts are available for spore germination, as was expected from the calculation of models of spread [26,40].…”
Section: Seasonal Spore Dispersalsupporting
confidence: 82%
“…A possible explanation of this incongruence may be related to the contrasting spore trapping mechanisms used in the two studies. The spore traps used here sample the particles occurring directly in the air by impaction on the adhesive surface, while the passive spore traps used by Garbelotto et al [28] and in other research [18,39] sample the spores passively deposited on a filter paper. Passive deposition may be supported by rainfall, as the rain drops trap the air inoculum and deliver it onto the surface of the filter paper.…”
Section: Effect Of the Meteorological Conditionsmentioning
confidence: 99%
“…Similar results with constant presence of F. circinatum along the whole year, were obtained in other areas such as northern California [24] and South Africa [35]. This finding means that F. circinatum in Galicia can develop the infection at any time of the year whenever suitable environmental conditions and susceptible hosts are available for spore germination, as it was expected from the calculation of models of spread [36,37].…”
Section: Seasonal Spore Dispersalsupporting
confidence: 84%
“…A possible explanation of this incongruence may be related to the contrasting mechanisms of the spore trapping used in the two studies. The spore traps used here sample the particles occurring directly in the air by impaction on the adhesive surface, while the passive spore traps used by Garbelotto et al [24] and other researchers [18,35] sample the spores passively deposited on a filter paper. Passive deposition may be supported by rainfall, during which the rain drops trap the air inoculum and deliver it onto the surface of the filter paper.…”
Section: Effect Of the Meteorological Conditionsmentioning
confidence: 99%
“…In South Africa, F. circinatum is associated with nursery and post-plant mortality of Pinus patula (Viljoen and Wingfield 1994, Mitchell et al 2004, Crous 2005, Mitchell et al 2011 has not yet been found causing classic pitch canker disease in plantations of this species despite classic pitch canker occurring in P. radiata plantations in South Africa (Coutinho et al 2007). Post-planting mortality of P. patula results from the transfer of F. circinatum with asymptomatic seedlings from the nursery (Crous 2005, Jones et al 2014. Effective control of the pathogen in the nursery is therefore necessary to address post-planting mortality associated with the pathogen.…”
Section: Introductionmentioning
confidence: 99%